Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1103/physrevlett.116.071102
|View full text |Cite
|
Sign up to set email alerts
|

End Point of Black Ring Instabilities and the Weak Cosmic Censorship Conjecture

Abstract: We produce the first concrete evidence that violation of the weak cosmic censorship conjecture can occur in asymptotically flat spaces of five dimensions by numerically evolving perturbed black rings. For certain thin rings, we identify a new, elastic-type instability dominating the evolution, causing the system to settle to a spherical black hole. However, for sufficiently thin rings the Gregory-Laflamme mode is dominant, and the instability unfolds similarly to that of black strings, where the horizon develo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(151 citation statements)
references
References 39 publications
(65 reference statements)
9
138
1
Order By: Relevance
“…Entropy arguments suggest that the evolution of unstable AdSSchw 5 × S 5 black holes would proceed towards the most dominant solution, which are the localised S 8 black holes. This entails a violation of cosmic censorship, much like in the evolution of the black string [42] or black ring [43]. Whether or not the evolution proceeds in this way, 5 is subdominant in entropy but nevertheless dynamically stable.…”
Section: ���mentioning
confidence: 99%
“…Entropy arguments suggest that the evolution of unstable AdSSchw 5 × S 5 black holes would proceed towards the most dominant solution, which are the localised S 8 black holes. This entails a violation of cosmic censorship, much like in the evolution of the black string [42] or black ring [43]. Whether or not the evolution proceeds in this way, 5 is subdominant in entropy but nevertheless dynamically stable.…”
Section: ���mentioning
confidence: 99%
“…It turns out that the only unstable mode in this case is the GL-like instability. However the case m Φ = O(1) is also important since now a new elastic-type (named by the property that this mode deforms the black ring without substantially changing its thickness) instability emerges, as first found by the numerical study in [41], and then by the large D study in [18] . To investigate the elastic instability, the O(1/n 2 ) corrections to the effective equations are required.…”
Section: Quasinormal Modesmentioning
confidence: 99%
“…However, the numerical study [41,42] showed that for neutral fat black ring in five dimensions the axisymmetric perturbations are unstable. It is natural to expect such phenomena exists for the charged black ring as well.…”
Section: Jhep04(2017)167mentioning
confidence: 99%
“…In particular, they can be unstable [1][2][3][4][5][6], violate black hole uniqueness [2,3,7,8] and also lead to a violation of weak cosmic censorship [9][10][11].…”
Section: Introductionmentioning
confidence: 99%